Democratic Republic of Sao Tome and Principe : First Review Under the Extended Credit Facility and Request for Augmentation of Access, Rephasing of Access, and Financing Assurances Review-Press Release; Staff Report; and Statement by the Executive Director for the Democratic Republic of Sao Tome and Principe. (IMF Staff Country Reports; Country Report ;, 2020)
The pandemic is taking a heavy toll on the fragile island nation of Sao Tome and Principe. Tourist arrivals came to an abrupt halt in mid-March, externally financed projects are being delayed, and supply shipments are disrupted. In response to the local outbreak, emergency confinement measures have been in place since March to contain infection. The authorities began phasing out these measures in late June, aiming for a full reopening of the economy by end-July. A disbursement supported by the Rapid Credit Facility (SDR 9.028 million) was approved in April 2020. The authorities request an augmentation of the ECF program by 10 percent of quota (SDR 1.48 million).